2012
DOI: 10.1089/pho.2010.2762
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG Laser Versus Systemic Metronidazole as an Adjunct to Nonsurgical Periodontal Therapy: A Clinical and Microbiological Study

Abstract: Within its limits, this study demonstrated the possibility of better resolution of infection with combined SRP+Er:YAG laser treatment. However, microbiological results failed to demonstrate significant advantages of this combination in comparison with SRP alone or SRP+systemic metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…In addition, our data also support the findings of Yilmaz et al. (, ), who observed that positive changes in clinical parameters such as attachment gain and PD reduction were significantly greater in the ERL + SRP group than the SRP group. Likewise, Saglam et al.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our data also support the findings of Yilmaz et al. (, ), who observed that positive changes in clinical parameters such as attachment gain and PD reduction were significantly greater in the ERL + SRP group than the SRP group. Likewise, Saglam et al.…”
Section: Discussionsupporting
confidence: 91%
“…, Yilmaz et al. , ). The smoking rate varied among selected studies, with five including non‐smoking populations.…”
Section: Resultsmentioning
confidence: 98%
“…All included studies were RCTs with a parallel design. One study did not report any information about the inclusion of smokers. Two studies reported that smokers were excluded from the studies.…”
Section: Resultsmentioning
confidence: 99%